ANALISIS PENGUNAAN KATA “ANJAY” YANG MENJADI KEBIASAAN GEN Z DAN GEN ALPHA DALAM BERKOMUNIKASI - Hardelia Rosidatul Adha; Aliyah Shafa N, Sinar Permata W.S., Abid Ubaidillah Akbar, Huda Hidayatulloh, Lintang Sinaring R (ADISAM PUBLISHER, 2025)
The use of language in communication among the younger generation, especially Gen Z and Gen Alpha, shows changes in the form and function of everyday language. One prominent phenomenon is the use of the words